COLOR IN PAINTING (IN PERSPECTIVE FROM PREHISTORIC TIMES TO PRESENT TIMES): चित्रकला में रंग (प्रागैतिहासिक काल से वर्तमान काल तक के परिप्रेक्ष्य में) - Gautam (International Journal of Research -GRANTHAALAYAH, 2014)
Varna (color) has an important place in human life. Each item has a different color. It is visible to us only because the objects are colored in the ground. Human attraction to colors has never decreased. That is why, from primitive cave paintings to modern humans, colors have been used in the development of beauty. The importance of colors is seen in every chapter of the history of human life. A picture can be made predominantly based on the color effect ie color effect. Color is an important part of our life; Without it, nature does not have any existence of any substance or organism present. It is only through colors that we recognize him. Color has its own existence, which has its own language and an artist understands that language very well. Only then does he use colors properly in chitrakala. मानव जीवन में वर्ण (रंग) का महत्वपूर्ण स्थान है। प्रत्येक वस्तु क¨ई न क¨ई रंग लिये हुये है। वस्तुअ¨ं के धरातल में रंग ह¨ने के कारण ही वह हमें दिखाई देती है। रंग¨ं के प्रति मानव का आकर्षण कभी घटा नहीं है। इसीलिये आदिम गुफाचित्र्ा¨ं से ल्¨कर आधुनिक मानव तक ने स©न्दर्य के विकास में रंग¨ं का सहारा लिया है। रंग¨ं का महत्व हमें मानव जीवन के इतिहास के हर अध्याय में देखने क¨ मिलता है। वर्ण प्रभाव अर्थात् रंग प्रभाव के आधार पर चित्र्ा क¨ स©न्दर्य प्रधान बनाया जा सकता है। रंग हमारे जीवन का महत्वपूर्ण हिस्सा है; इसके बिना प्रकृति उपस्थित किसी भी पदार्थ या जीव का अपना क¨ई वजूद नहीं है। रंग¨ं के द्वारा ही हमें उसकी पहचान ह¨ती है। रंग का अपना एक अस्तित्व है जिसकी अपनी ही एक भाषा है अ©र उस भाषा क¨ एक कलाकार बहुत अच्छे से समझता है। तभी वह रंग¨ं का प्रय¨ग उचित ढंग से चित्र्ाकला में करता है।